2004
DOI: 10.1081/lpr-120039717
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Enrofloxacin in Liposomes I: Preparation and In Vitro Characterization of LUV

Abstract: Liposomes are effectively used in the treatment of microbial infections. Higher cellular uptake has been reported when antibiotics are encapsulated in liposomes. In this study, enrofloxacin (ENF) was encapsulated in large unilamellar vesicles (LUVs) and the effects of formulation variables on the liposome characteristics were investigated. Liposomes were prepared using dry lipid film method. A number of variables such as molar ratios of phospholipid (DPPC; DL-alpha-phosphatidylcholine dipalmitoyl), cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…We suggest that increasing the drug encapsulation capacity produced the slow release of ENR. This result was similar to the results found in the literature 3,13,14 . The optimized LUVs with the appropriate particle size and distribution, high surface charge and drug release properties used in the in vitro studies were chosen for use in the in vivo experiments, and the treatment efficacy on rats with experimental pneumonia was partially investigated.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We suggest that increasing the drug encapsulation capacity produced the slow release of ENR. This result was similar to the results found in the literature 3,13,14 . The optimized LUVs with the appropriate particle size and distribution, high surface charge and drug release properties used in the in vitro studies were chosen for use in the in vivo experiments, and the treatment efficacy on rats with experimental pneumonia was partially investigated.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, ENR-loaded MLVs and LUVs, which were prepared using the optimum formulations of our previous studies 13,14 , were given to rats with experimental pneumonia, and we evaluated the efficiency of the liposomal treatment. The characterization of the liposomes' shape and surface was evaluated using a transmission electron microscope (TEM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro drug release was carried out in triplicate for each preparation and expressed as Mean ± SD., and then the cumulative drug release (%CDR) was calculated and a plot of time versus %CDR was constructed and shown graphically. In vitro skin permeation studies were conducted for all liposome formulations and reported (Panigrahi et al 2006;Sezer et al 2004;Agarwal et al 2014).…”
Section: In Vitro Drug Releasementioning
confidence: 99%